Parasites - Halvor Mehlum; Karl Ove Moene; Ragnat Torvik (University of Oslo, Department of Economics, 2003)
Unproductive enterprises that feed on productive businesses, are rampant in developing countries. These parasitic enterprises take divergent forms, some headed by violent bandits and brutal mafia bosses, others by organized middlemen or smart political insiders. All of them seem to have the profit motive in common. A consequence of parasitic enterprises is that societies may be locked into a self enforcing configuration of beliefs and practices that result in persistent poverty. In some instances the parasites are former youth gangs or rebel groups that are transformed to criminal enterprises feeding on private businesses (Collier 2000). Such bandits not only extort and control small-scale informal enterprises, street sellers and sweat shops, but the most professional among the plunderers prey on large-scale modern firms. One case in point is the lucrative businesses of kidnapping and extortion in Colombia, where guerrillas collect more than hundred million US dollars per year only from the oil industry alone (Hunter, 1996). Other parasitic enterprises act like a Mafia, providing protection, enforcing contracts, and mediating disputes for money. These enterprises apply force on a commercial basis to collect debt and enforce business contracts. ”Problem solving” that normally belongs to the realm of the state is undertaken by violent entrepreneurs and their gangs, where the targets have to pay tributes to avoid damages. Even though these predatory forms of illegal activities can be found in industrialized countries – with the Sicilian and the We thank Kaushik Basu for productive discussions. We have also benefitted from useful comments by Sam Bowles and Karla Hoff. We are grateful for support from the Norwegian Research Council. 1 Parasites 2 American Mafia the best-known examples– they are more prevalent and more burdensome in developing countries and in the transition economies of Eastern Europe and the former Soviet Union. In the transition countries the institutional vacuum created by the collapse of communism has opened the scene for extortion by such mafia-like parasites. Their activities belong to the growing shadow economy (Campos 2000). One example is private enforcement of business contracts, by threat of violence from criminal gangs, that became routine in the Russian business world in the 1990s. As Volkov observed, “[b]efore signing formal business contracts, companies acquire information on each other's enforcement partners (whom do you work with?)”(Volkov 1999 p.746). Such criminal gangs can obtain a considerable influence over private businesses. According to the Russian Ministry of Internal Affairs, criminal gangs in 1994 controlled 40,000 Russian businesses (Volkov 1999). Parasitic enterprises can also be run by middlemen who organize marketing boards with substantial monopsony power, or by wealthy land-owners who provide credit at exploitative interest rates. Political insiders set up their own parasitic enterprises that private sector companies have to consult and remunerate in order to have certain contracts signed. These activities, sometimes called straddling, are common in Africa. In Kenya, for example, president Moi allowed extensive straddling among politicians and bureaucrats in exchange for loyalty to the government (Bates 1983, Bigsten and Moene 1996). Finally, parasites are not always private enterprises, but can be found as corrupt politicians and bureaucrats who collect bribes and use their positions for own private benefit. All these kinds of parasitic rent appropriation activities that are directed towards private businesses flourish in the absence of a state that effectively protects property rights, and enforces contracts. Thus parasitic rent appropriation is different from regular rent-seeking that captures activities directed towards an active state undertaking regulations that private businesses wish to avoid or benefit from. While regular rent seeking distort political decisions via wasteful influence activities, parasitic rent appropriation challenges the state's monopoly of taxation, protection and legitimate violence. In this paper we highlight some of the causes and consequences of these parasitic behaviors. Our basic claim is based on the premise that entrepreneurs of both productive and parasitic enterprises to some extent are drawn from the same limited pool of entrepreneurs. Parasites 3 When this is the case, the rise of parasitic profit opportunities may cause economic stagnation and underdevelopment that in turn enhance the profitability of parasitic enterprises relative to productive enterprises. Thus parasitic rent appropriation may induce stagnation, while stagnation may induce parasitic activities. Together the two links can lead developing economies into a poverty trap. In order to study the consequences of parasitic profit opportunities, we embed parasitic activities within a big-push model of industrialization. Parasitic activities compete for scarce entrepreneurial resources, as in the seminal papers on the misallocation of talent to unproductive activities by Usher (1987), Baumol (1990), Murphy, Shleifer, and Vishny (1991 and 1993), and Acemoglu (1995).1 First, however we clarify what we mean by a poverty trap and how it is related to the concepts of strategic complementarity.
Keywords: K42; O17; 330; Developing countries; parasitic enterprises; criminal gangs; Organisierte Kriminalität; Entwicklungsländer; Ökonomische Sicherheit